(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
In developing economies, public debt has increasingly been used as a fiscal policy instrument to finance development objectives amid revenue shortfalls, raising concerns about its effectiveness in delivering long-term economic development. Thus, this study investigated the impact of public debt on economic development in Nigeria over the period 1986 to 2023. The study employed time series data on economic development, proxied by the human development index, external debt, domestic debt, gross domestic saving, and oil revenue collected from the Central Bank of Nigeria Annual Statistical Bulletin, World Bank Development Indicators, and the Debt Management Office, Nigeria. In the analysis, descriptive statistics, trend analysis, unit root test, and autoregressive distributive lag technique were employed. The cointegration test revealed that a long-run equilibrium relationship exists among the variables. From the empirical evidence, external debt had a negative and significant impact on economic development, while domestic debt had a positive but insignificant impact on economic development. In conclusion, the study highlights that domestic debt has a more favorable association with development outcomes, while external debt poses risks if not properly managed. Based on the findings, the study recommended, among others, the government should adopt debt ceiling policies, as well as effective debt sustainability frameworks. The public procurement reform should be sustained and strengthened. This will encourage due process in government dealings. Also, there is a need for the government to partner with civil society organizations to monitor how external debt is being distributed and expended.